(untitled) (International Journal of Engineering and Computer Science, 2014)
In this paper we have discuss the Biometrics security .The biometrics term is becoming highly important in computer security world. The human physical Characteristics like fingerprints, face, hand geometry, voice and iris are known as biometrics. Biometrics is the today’s high security application help for the minimized the error system rate and unauthorized access. In this term paper discuss about the future and present use of Biometrics security and various type of the Biometrics